The Impact of Lean, Green, and Agile Supply Chain Practices on Supply Chain Responsiveness and Its Influence on Green Competitive Advantage: A Quantitative Analysis of Indonesian SMEs - Pramita Putri, Devi Lestari; Furqon, Mohammad Amir; Salamah, Siti Nikmatus; Toyyibah, Nurul; Mukarromah, Syarina Jazilatul (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the influence of Lean Supply Chain Practices (LSCP), Green Supply Chain Practices (GSCP), and Agile Supply Chain Practices (ASCP) on Green Competitive Advantage (GCA) in Small and Medium Enterprises (SMEs) in Bangkalan and Sampang districts, Indonesia. Additionally, the research explores the mediating role of Supply Chain Responsiveness (SCR) in strengthening the relationship between these practices and GCA. A quantitative approach was employed using a structured questionnaire distributed to 499 SME managers in the targeted regions. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS software, testing both direct and indirect relationships among variables. Judgment sampling was applied to select respondents, ensuring relevance to the research context. The findings indicate that LSCP, GSCP, and ASCP significantly enhance Green Competitive Advantage through their direct effects. Furthermore, SCR was found to mediate the relationships between these practices and GCA, demonstrating its critical role in facilitating adaptability and responsiveness to market changes. This study fills a gap in the literature by integrating three supply chain practices (Lean, Green, and Agile) in a single model, emphasizing the role of SCR as a mediating variable, which has been underexplored in the context of SMEs. The study’s findings have practical implications for SMEs, suggesting that integrating these supply chain practices can improve their sustainability and competitiveness. Future research should consider expanding the model to include other mediators or moderating factors, such as digital transformation.